2014
DOI: 10.1016/j.jacc.2014.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Rotor Stability Separates Sustained Ventricular Fibrillation From Self-Terminating Episodes in Humans

Abstract: Objective We mapped human ventricular fibrillation (VF) to define mechanistic differences between episodes requiring defibrillation versus those that spontaneously terminate. Background VF is a leading cause of mortality, yet episodes may also self-terminate. We hypothesized that the initial maintenance of human VF is dependent upon the formation and stability of VF rotors. Methods We enrolled 26 consecutive patients (age 64±10 years, n=13 with LV dysfunction) during ablation procedures for ventricular arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 29 publications
2
51
0
Order By: Relevance
“…More recent work using endocardial basket electrodes demonstrated that rotational activity is present in the vast majority of patients following induction of VF and that the stability of the rotors is larger in patients with sustained VF episodes compared to patients with self-terminating ones (19). A critical element in that study was the manual interpretation of animated sequences of phase maps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent work using endocardial basket electrodes demonstrated that rotational activity is present in the vast majority of patients following induction of VF and that the stability of the rotors is larger in patients with sustained VF episodes compared to patients with self-terminating ones (19). A critical element in that study was the manual interpretation of animated sequences of phase maps.…”
Section: Discussionmentioning
confidence: 99%
“…Separately, spiral wave reentry (rotors), focal sources, and disorganized activity have been described in human VF (46), but the relative importance of each was unclear. Recent work in our laboratory mapped human VF and demonstrated that spiral waves, identified visually from computed phase maps, were present in the majority of patients (7). Furthermore, this study found that sustained episodes requiring defibrillation to terminate were characterized by greater spiral wave stability (7), and that ablation of VF sources increased the VF threshold in an animal model and patient with clinical VF (8).…”
Section: Introductionmentioning
confidence: 99%
“…(30) However, filaments may adopt varying other shapes (e.g., L-shape, U-shape or O-shape) that may generate different patterns of activation at each surface, but still underlie a scroll wave within the three-dimensional structure of the atrial or ventricular myocardium (Figure 1). (11,31) The orientation of the filament may also change, which introduces additional complexity when it comes to attempting to track rotors in three-dimensions. Computer simulations have shown that after a certain transitional period, the filament aligns with the local fiber orientation, which provides support to the presence of intramural reentry.…”
Section: Rotor Formation and Substrate Related-stabilitymentioning
confidence: 99%
“…(34) Sometimes they meander within specific regions of the myocardial tissue. (11) Other times, one end of a scroll wave filament (e.g., on the epicardium) may meander while the other end (i.e., on the endocardium) remains anchored. Recent data by Krummen et al underscored the importance of rotor stationarity in sustaining VF episodes that eventually require defibrillation.…”
Section: Rotor Formation and Substrate Related-stabilitymentioning
confidence: 99%
“…While rotors had been observed in animal models [70, 71] and human VF [7274], until recently [7•, 75–78, 79•] there was little or no evidence for rotors in human AF. Several features of human AF may have contributed to difficulties in arrhythmia mapping, including low-amplitude signals [80], the practice of recording from a limited number of simultaneous electrodes during AF despite its spatial heterogeneity, the use of clinical bipolar signals during AF [81], and dependence upon activation-based analysis of AF, rather than phase mapping [82].…”
Section: Af Maintenancementioning
confidence: 99%